Compendium of Surface and Interface Analysis - The Surface Science Society of Japan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book concisely illustrates the techniques of major surface analysis and their applications to a few key examples.  Surfaces play crucial roles in various interfacial processes, and their electronic/geometric structures rule the physical/chemical properties. In the last several decades, various techniques for surface analysis have been developed in conjunction with advances in optics, electronics, and quantum beams. This book provides a useful resource for a wide range of scientists and engineers from students to professionals in understanding the main points of each technique, such as principles, capabilities and requirements, at a glance. It is a contemporary encyclopedia for selecting the appropriate method depending on the reader's purpose. .
Acoustic Microscopy -- Action Spectroscopy with STM -- Ambient Pressure X-ray Photoelectron Spectroscopy -- Angle-resolved Ultraviolet Photoelectron Spectroscopy -- Atom Probe Field Ion Microscope -- Atomic Force Microscope -- Auger electron spectroscopy -- Cathodoluminescence -- Conductive Atomic Force Microscopy -- Differential Interference Contrast Microscopy/Phase-Contrast Microscopy -- Dynamic Secondary Ion Mass Spectrometry -- Elastic Recoil Detection Analysis -- Electrochemical Atomic Force Microscopy -- Electrochemical Infrared Spectroscopy -- Electrochemical Scanning Tunneling Microscopy -- Electrochemical Second Harmonic Generation -- Electrochemical Sum Frequency Generation -- Electrochemical Surface X-ray Scattering -- Electrochemical Transmission Electron Microscopy -- Electrochemical X-ray Absorption Fine Structure -- Electrochemical X-ray Photoelectron Spectroscopy -- Electron Backscatter Diffraction -- Electron Energy Loss Spectroscopy -- Electron Probe Microanalysis -- Electron Stimulated Desorption -- Electron-beam-induced current -- Ellipsometry -- Environmental SEM (Atmospheric SEM) -- Environmental Transmission Electron Microscopy -- Extended X-ray Absorption Fine Structure -- Focused Ion Beam Scanning Electron Microscope -- Force Curve -- Force Spectroscopy -- Frequency-Modulation Atomic Force Microscopy -- Gap Mode Raman Spectroscopy -- Glow Discharge Mass Spectrometry -- Glow Discharge Optical Emission Spectrometry -- Hard X-ray Photoelectron Spectroscopy -- Helium Atom Scattering -- High-resolution Elastic Recoil Detection Analysis -- High-resolution electron energy loss spectroscopy -- High-resolution Rutherford Backscattering Spectrometry -- High-Speed Atomic Force Microscopy -- Imaging Ellipsometry -- Impact Collision Ion Scattering Spectroscopy -- Inelastic Electron Tunneling Spectroscopy -- Infrared External-Reflection Spectroscopy -- Infrared Reflection Absorption Spectroscopy -- Interferometer displacement measurement -- Inverse Photoemission Spectroscopy -- Kelvin Probe Force Microscope -- Laser Ionization Secondary Neutral Mass Spectrometry -- Laser Photoelectron Spectroscopy -- Lateral Force Microscopy -- Liquid SPM/AFM -- Low Energy Ion Scattering Spectroscopy -- Low-Energy Electron Diffraction -- Low-Energy Electron Microscope -- Magnetic Force Microscopy -- Matrix-Assisted Laser Desorption/Ionization -- Medium Energy Ion Scattering -- Micro Raman Spectroscopy -- Microprobe Reflection High Energy Electron Diffraction -- Multiple-probe Scanning Probe Microscope -- Nanoscale Angle-resolved Photoelectron Spectroscopy -- Nonlinear Spectroscopy -- Nuclear Reaction Analysis -- Optical Microscopy -- Optical second harmonic generation spectroscopy and microscopy -- Particle Induced X-ray Emission -- Penning Ionization Electron Spectroscopy -- Phase Mode SPM/AFM -- Photoelectron diffraction -- Photoelectron holography -- Photoelectron Yield Spectroscopy -- Photoemission Electron Microscope -- Photoluminescence -- Photon Emission from the Scanning Tunneling Microscope -- Photo-StimulatedDesorption -- Piezoresponse Force Microscope -- Positron-Annihilation-Induced Desorption -- p-Polarized Multiple-Angle Incidence Resolution Spectrometry -- Quartz Crystal Microbalance -- Reflectance Difference Spectroscopy -- Reflection High-Energy Electron Diffraction -- Resonant Inelastic X-ray Scattering -- Rutherford Backscattering Spectrometry -- Scanning Capacitance Microscopy -- Scanning Electrochemical Microscopy -- Scanning Electron Microscope Energy Dispersive X-ray Spectrometry -- Scanning Electron Microscopy -- Scanning Helium Ion Microscope -- Scanning Near-field Optical Microscopy/ Near-field Scanning Optical Microscopy -- Scanning Probe Microscopy -- Scanning Transmission Electron Microscopy -- Scanning Transmission X-ray Microscopy -- Scanning Tunneling Microscopy -- Scanning Tunneling Spectroscopy -- Soft X-ray Absorption Fine Structure -- Spectroscopic Ellipsometry -- Spin- and Angle-resolved Photoelectron Spectroscopy -- Spin-Polarized Scanning Electron Microscopy -- Spin-Polarized ScanningTunneling Microscopy -- Spin-resolved Photoemission Electron Microscopy -- Super-resolution Microscopy -- Surface acoustic wave -- Surface Enhanced Raman Scattering -- Surface Magneto-optic Kerr Effect -- Surface Plasmon Resonance -- Surface Profilometer -- Surface Sensitive Scanning Electron Microscopy -- Surface X-ray Diffraction -- Surface-enhanced Infrared Absorption Spectroscopy -- Synchrotron Radiation Photoelectron Spectroscopy -- Synchrotron Scanning Tunneling Microscope -- Thermal desorption spectroscopy -- Time-of-Flight Secondary Ion Mass Spectrometry -- Time-resolved Photoelectron Spectroscopy -- Time-resolved Photoemission Electron Microscopy -- Time-resolved Scanning Tunneling Microscopy -- Tip-Enhanced Raman Scattering -- Total Reflection X-Ray Fluorescence -- Transmission Electron Diffraction -- Transmission Electron Microscope -- Ultraviolet Photoelectron Spectroscopy -- Ultraviolet-visible spectrophotometry -- Vibrational Sum Frequency Generation Spectroscopy -- X-ray Absorption Near Edge Structure -- X-ray aided noncontact atomic force microscopy -- X-ray Crystal Truncation Rod Scattering -- X-ray Magnetic Circular Dichroism -- X-ray Photoelectron Spectroscopy -- X-Ray Reflectivity -- X-ray Standing Wave Method.
Keywords: Materials -- Analysis; Spectrum analysis; Surfaces (Physics).; Surfaces (Technology).; Thin films; Characterization and Analytical Technique; Spectroscopy; Surface and Interface and Thin Film; Surfaces, Interfaces and Thin Film